2011
DOI: 10.1002/mrm.22856
|View full text |Cite
|
Sign up to set email alerts
|

Arterial input functions determined from MR signal magnitude and phase for quantitative dynamic contrast‐enhanced MRI in the human pelvis

Abstract: Dynamic contrast-enhanced (DCE) MRI is often used to measure the transfer constant (Ktrans) and distribution volume (ve) in pelvic tumors. For optimal accuracy and reproducibility, one must quantify the arterial input function (AIF). Unfortunately, this is challenging due to inflow and signal saturation. A potential solution is to use MR signal phase (ϕ), which is relatively unaffected by these factors. We hypothesized that phase-derived AIFs (AIFϕ) would provide more reproducible Ktrans and ve values than mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
2
20
1
Order By: Relevance
“…This is expected because phase-derived VIF is less sensitive to inflow effects. 9 Even though 3D gradientrecalled echo sequences are less sensitive to inflow than 2D gradient-recalled echo, perfusion values obtained with the phase method also had lower coefficients of variation than the ones obtained from the SI method. The use of bookend T1 measurements with the phase technique could also have contributed to an improvement in the calculations of perfusion values because this technique can presumably provide more accurate estimation of the gadolinium concentration in tumors.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is expected because phase-derived VIF is less sensitive to inflow effects. 9 Even though 3D gradientrecalled echo sequences are less sensitive to inflow than 2D gradient-recalled echo, perfusion values obtained with the phase method also had lower coefficients of variation than the ones obtained from the SI method. The use of bookend T1 measurements with the phase technique could also have contributed to an improvement in the calculations of perfusion values because this technique can presumably provide more accurate estimation of the gadolinium concentration in tumors.…”
Section: Discussionmentioning
confidence: 92%
“…8,9,15 For that reason, some authors have proposed performing 2 injections of 0.05 mmol/kg of gadolinium for DCE MR imaging to minimize the error arising from the conversion of signal intensity to gadolinium concentration from magnitude images. 16 While saturation of signal intensity could lead to an underestimation of the contrast agent concentration, the presence of inflow effects could lead to an overestimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that error in estimating the initial AIF amplitude can propagate into the resulting parameter estimates (90) and various innovative approaches have been proposed for sampling the AIF, such as the use of a low-dose prebolus (91) and the MR signal phase (92). However, accurate measurement of the AIF from DCE MRI data can be challenging in situations such as the absence of a suitable artery in the imaging field of view, low signal-tonoise, and partial volume effects for small arteries.…”
Section: Reference Region (Rr) Methodsmentioning
confidence: 99%
“…However, the required large arterial vessel within the depicted field of view may not exist if small lesion areas, e.g., breast cancer, are imaged. Also, the accuracy of the measured AIF depends on the chosen MRI pulse sequence parameters [158], namely, the optimization of temporal resolution for determining the AIF accurately could result in undesirable spatial resolution and signal-to-noise ratio (SNR) [155]. It is worth mentioning that the AIF obtained from a feeding artery characterizes the whole arterial blood and must be corrected to account for the hematocrit factor in order to represent the plasma concentration.…”
Section: Arterial Input Function (Aif)mentioning
confidence: 99%